2001
DOI: 10.2337/diacare.24.11.1972
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Nephrotic-Range Albuminuria in Type 1 Diabetic Patients

Abstract: OBJECTIVE -To evaluate the cumulative incidence of nephrotic-range albuminuria (NRA), the frequency of remission, and the impact on progression, we analyzed data from a prospective cohort study of type 1 diabetic patients with diabetic nephropathy.RESEARCH DESIGN AND METHODS -All of the albuminuric type 1 diabetic patients (n ϭ 321, 121 women), who had at least yearly measurements of glomerular filtration rate (GFR) with a 51 Cr-EDTA plasma clearance technique and were followed for at least 3 years, were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
(56 reference statements)
6
45
0
Order By: Relevance
“…Remission was defined as albuminuria <200 microg/min sustained for at least one year and a decrease of at least 30% from preremission levels, and regression as rate of decline in GFR equal to the natural aging process: < or =1 ml/min/year during the investigation period in this report. Moreover, remission of nephrotic-range albuminuria in type 1 diabetic patients was also reported at Steno Diabetes Center (35). In this report, remission was induced in 28 of 126 (22%) patients; 21 were predominantly treated with angiotensin converting enzyme (ACE) inhibitors, 7 with non-ACE inhibitor medications.…”
Section: Clinical Impacts Of Albuminuria and Gfr On The Prognosis In mentioning
confidence: 81%
“…Remission was defined as albuminuria <200 microg/min sustained for at least one year and a decrease of at least 30% from preremission levels, and regression as rate of decline in GFR equal to the natural aging process: < or =1 ml/min/year during the investigation period in this report. Moreover, remission of nephrotic-range albuminuria in type 1 diabetic patients was also reported at Steno Diabetes Center (35). In this report, remission was induced in 28 of 126 (22%) patients; 21 were predominantly treated with angiotensin converting enzyme (ACE) inhibitors, 7 with non-ACE inhibitor medications.…”
Section: Clinical Impacts Of Albuminuria and Gfr On The Prognosis In mentioning
confidence: 81%
“…A clear reduction in the incidence of macrovascular and microvascular end points was also documented in the UKPDS trial that compared tight BP control with either captopril or atenolol (defined as Ͻ150/85) versus usual, although a large part of the reduction of microvascular complications was due to a reduction in retinal photocoagulation (23). However, Parving et al (24) found that tight BP control was associated with remission of type 1 diabetic nephropathy, and Weidman et al (25) found a strong relation between the degree of BP reduction and reduction in proteinuria in diabetic nephropathy.…”
Section: Bp Controlmentioning
confidence: 99%
“…2,3 Control of blood pressure and proteinuria are the most important interventions in order to slow the rate of deterioration in renal functions. [4][5][6] The activation of renin-angiotensin-aldosterone system (RAAS) had been shown to play a key role in both systemic and glomerular hypertension and also proteinuria. RAAS blockers are effective in slowing the progression of CKD independent of their antihypertensive effects.…”
Section: Introductionmentioning
confidence: 99%